Guías de almas. - Vaca, César, O.S.A (Editorial Senén Martín, 1949)
Prólogo -- 5 - Ante la Segunda Edición -- 8 - Introducción -- 9 - I. - La Vocacion -- 25 - II. - La Persona -- 119 - III. - La Ciencia -- 197 - IV. - El Sexo -- 263